Standard EEG: A Research Roadmap for Neuropsychiatry - Boutros, Nash N. (Springer International Publishing : Imprint: Springer, 2013)
This volume is designed to serve as a reference source containing both historical and recent references with a special focus on the existing gaps of knowledge regarding EEG deviations in psychiatric populations. Every chapter begins by outlining the clinical issues, then reviews available literature and concludes by highlighting a) currently supportable findings, and b) open research questions. In some chapters the author makes suggestions regarding the research design that will most likely lead to generating data that can move the field towards resolving unresolved issues.